Leukotrienes as a molecular link between obstructive sleep apnoea and atherosclerosis. (7th November 2013) - Stanke-Labesque, Françoise; Pépin, Jean-Louis; Gautier-Veyret, Elodie; Lévy, Patrick; Bäck, Magnus
Abstract: Leukotrienes are biologically active lipid mediators of inflammation involved in atherogenesis. Obstructive sleep apnoea (OSA) patients exhibit early atherosclerosis and activation of the leukotriene pathway. In OSA patients, the production of leukotrienes is increased in relation to OSA severity and in vitro exposure of immune cells to intermittent hypoxia increases leukotriene pathway transcription. Moreover, the leukotriene transcriptional pathway is associated with early vascular remodelling. Lastly, obesity is a major confounding factor for leukotriene activation in OSA. The aim of this review was to focus on the intricate network of leukotrienes, chronic intermittent hypoxia, and atherosclerosis, with an emphasis on the role of leukotrienes in the early atherosclerosis observed in OSA patients.